2014
DOI: 10.3892/ol.2014.2113
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 single-nucleotide polymorphisms Asp299Gly and Thr399Ile in ovarian cancers

Abstract: Toll-like receptor (TLR4) 4 is present in numerous cell types and serves as the first point of defense in the innate immune system. Single-nucleotide polymorphisms (SNPs) are present in a number TLR genes and have been associated with various infection and inflammation disorders. Asp299Gly and Thr399Ile, TLR4 SNPs, are associated with tumor progression. In the present study, cases of ovarian cancer were analyzed with regards to Asp299Gly and Thr399Ile of the TLR4 gene. Genotype analysis was performed using DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The TLR4 Asp299Gly and Thr399Ile alleles were not detected in the 105 ovarian cancer patients in a study conducted in northern China. These results indicate that the TLR4 299Gly and 399Ile alleles were exhibited at a lower frequency in northern Chinese ovarian cancer patients compared to other studies [103]. Among the 70 women with ovarian cancer enrolled in the Poland study, the heterozygous variant and the recessive G allele of rs4986790 were more frequently found than in the 130 healthy individuals, indicating an increased risk of OC for its carriers.…”
Section: Discussionmentioning
confidence: 52%
“…The TLR4 Asp299Gly and Thr399Ile alleles were not detected in the 105 ovarian cancer patients in a study conducted in northern China. These results indicate that the TLR4 299Gly and 399Ile alleles were exhibited at a lower frequency in northern Chinese ovarian cancer patients compared to other studies [103]. Among the 70 women with ovarian cancer enrolled in the Poland study, the heterozygous variant and the recessive G allele of rs4986790 were more frequently found than in the 130 healthy individuals, indicating an increased risk of OC for its carriers.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, the TLR4 Asp299Gly polymorphism was detected in 15.0% (6/40) of women with HGSOC. The distribution of Asp299Gly and Thr399Ile was earlier analyzed in 105 Chinese women with OC, but these polymorphisms were not detected in the studied populations [75]. Several studies have confirmed the absence of rs4986790 in the Chinese population and a low prevalence of this SNP in Asian populations [39].…”
Section: Discussionmentioning
confidence: 91%
“…(rs4986791) in the Chinese population. They found that in ovarian cancer patients, rs4986790 and rs4986791 presented at a lower incidence [58]. Related to gastric cancer, a meta-analysis done by Zhou et al demonstrated that TLR4 + 896AA/G and + 1196C/T polymorphisms may be associated with significantly increased gastric cancer risk among the Caucasian population [59].…”
Section: • Potential Association Between Tlr4 Polymorphisms and Cancementioning
confidence: 99%